Analysis of the motivation, attitude and participation in extracurricular physical activity - José Arturo Abraldes Valeiras; Francisco M. Argudo Iturriaga (FEADEF, 2009)
The current essay tries to evaluate the effect of the styles of teaching about participation and motivation among the students of Physical Education in the third year of secondary education. A quasi-experimental design was carried out in a group of 30 students, and it was divided into two subgroups, A and B, of 15 students, to which it will be applied the traditional teaching style (of direct lead character) to the subgroup A, and a style that will promote the participation of the subgroup B. The experimental essay covered a total of 9 practical sessions of Physical Education in a school of secondary education. An attitude questionnaire towards physical activity was done before starting and finishing the educational unit of games and sports, to value if any kind of modification was produced in the behaviour of the students; and a satisfaction-motivation questionnaire at the end of each section of sessions. Variables subject of the study will be: traditional teaching style of direct lead and styles that help to socialization, motivation, participation, attitude and satisfaction.